IMPLEMENTASI METODE BERMAIN DAN MODIFIKASI MEDIA HASIL BELAJAR PASSING ATAS BOLA VOLI - Hidayat, Ace Tedi; Rahman, Ramdhani (Journal of Physical Education and Sport Science, 2025)
This research aims to determine the implementation of playing methods and media modifications in volleyball passing at SMP N 1 Cibeureum. This research is quantitative research with the design used is One Group pretest-posttest design. The subjects of this research were extracurricular students at SMP N 1 Cibeureum, and the sample used was 20 students. The research instrument used was a test on students in carrying out upper passing learning. The results of the research obtained tcount of Implementation of Playing Method of 11.560 and tcount of Modification of 8.263. Both of these tcount results were greater than the ttable of 1.725. Therefore, the value of tcount > ttable means that it can be concluded that the method of implementing Playing Methods and Media Modifications in Volleyball Top Passing can improve the top passing ability of extracurricular students at SMP N 1 Cibeureum. The magnitude of the increase in upper passing ability, after being given training in the Implementation of Playing Methods and Media Modifications in Volleyball Upper Passing for extracurricular students at SMP N 1 Cibeureum.